Textual Meaning in Three Most Viewed Ted Talks - Khairunnisa Khairunnisa; Iwa Lukmana; Riesky Riesky (Passage, 2021)
Public speaking has become a necessary skill to have and it gains a lot of interest from people. There are numerous public speaking line-ups available on the internet and one of the platforms is the TED website which provides TED Talks. This study focused on how Textual Meanings are realized in three most viewed TED Talks. The data were taken from TED website www.ted.com, which were taken in July 2020. Three titles were taken, namely ‘Do schools kill creativity?’ by Sir Ken Robinson, ‘This is what happens when you reply to spam email’ by James Veitch, and ‘Your body language may shape who you are’ by Amy Cuddy. This study used a descriptive qualitative method. Theory of textual meaning proposed by Halliday and Matthiessen (2004) and theory of public speaking by Schreiber and Hartranft (2013) are used. It is found that in three most viewed TED talks that Topical Theme is the most frequently used theme. Topical Theme appears 931 times (58.89%). Textual Theme appears 529 times (33.46%), and Interpersonal Theme appears 121 times (7.65%).Keywords: Public speaking, TED Talk, textual meaning, theme and rheme